Condiciones turísticas y su relación con la satisfacción de los visitantes del destino turístico Quistococha - Iquitos 2018 - Jimenez Saldaña, Anthony Gabriel (2019)
This research entitled: Tourist conditions and their relationship with the satisfaction of visitors to the Quistococha tourist destination - Iquitos 2018. Its main objective was to establish the correlation between the mentioned variables; Therefore, the type of research was deductive, with a correlational design, for which a population of 6,743 people has been taken, since a very large sample has been calculated, being made up of 364 tourists, also using a survey as a technique and a questionnaire as instruments, which after collecting the information has concluded that: tourist conditions are adequate (63%) because according to the perception of tourists visiting Quistococha greatly appreciate the attention, respect for the Identity, solidarity and kindness, however it considers that there are irregularities (34%) in terms of infrastructure and security of the place, they also qualify as regulating the dish and hospitality offered by the destination, also qualifies the means of transport. On the other hand, it has been determined that the visitor demonstrates an average level of satisfaction as 46% prove to be little satisfied and another 40% prove to be satisfied. It has been finally determined that tourist conditions are significantly related to the satisfaction of visitors to the tourist destination Quistococha - Iquitos 2018; this corroborated with the correlation coefficient of 0.991.